Design and Experimental Evaluation of a Rotary Knife-Type Device for Chopping Film-Mixed Residues - Jia Zhang; Jianhua Xie; Yakun Du; Weirong Huang; Yong Yue (Agriculture)
To address the resource utilization challenges of residual plastic film in Xinjiang and the issues of low reliability, poor cutting length qualification rates, and high energy consumption in existing film-mixed residue choppers, a rotary knife-type mixed film residue chopper was designed based on the “single support cutting + sliding cutting” principle. The device primarily consists of an adaptive feeding mechanism, a chopping mechanism, and a transmission system. The main structural and motion parameters of the mechanisms were determined through the analysis of feeding and chopping conditions. The primary factors affecting the cotton stalk chopping length qualification rate (CLCR-CS), residual film chopping length qualification rate (CFCR-RF), and specific energy consumption (SEC) were identified as the feeding roller speed, chopper speed, and the gap between the moving and fixed blades. Vibration characteristic analysis of the chopper was conducted using ANSYS software. The first six natural frequencies of the chopper were found to range from 112.54 to 186.65 Hz, with maximum deformation ranging from 0.885 to 1.237 mm. The excitation frequency was significantly lower than the first natural frequency, ensuring that the chopper met reliability and operational performance standards. A prototype was fabricated, and a second-order rotational orthogonal experiment was performed with CLCR-CS, CFCR-RF, and SEC as the test indicators and feeding roller speed, chopper speed, and the gap between the moving and fixed blades as the experimental factors. Variance and response surface analyses were conducted using Design-Expert software to clarify the effects and interactions of experimental factors on the test indicators. The second-order polynomial response surface model was optimized, and the optimal factor values were derived based on practical operational conditions. Verification experiments confirmed that the optimal operating parameters were a feeding roller speed of 32.40 r/min, a chopper speed of 222.0 r/min, and a blade gap of 1.0 mm. Under these conditions, CLCR-CS was 89.96%, CFCR-RF was 91.62%, and SEC was 5.36 kJ/kg, meeting the design specifications of the mixed film residue chopper.